Stent versus Coronary Artery Bypass Surgery in Multi-Vessel and Left Main Coronary Artery Disease: A Meta-Analysis of Randomized Trials with Subgroups Evaluation - Andrade,Pedro José Negreiros de (2019)
Abstract Background: Comparison between percutaneous coronary intervention (PCI) using stents and Coronary Artery Bypass Grafting (CABG) remains controversial. Objective: To conduct a systematic review with meta-analysis of PCI using Stents versus CABG in randomized controlled trials. Methods: Electronic databases were searched to identify randomized trials comparing PCI using Stents versus CABG for multi-vessel and unprotected left main coronary artery disease (LMCAD). 15 trials were found and their results were pooled. Differences between trials were considered significant if p < 0.05. Results: In the pooled data (n = 12,781), 30 days mortality and stroke were lower with PCI (1% versus 1.7%, p = 0.01 and 0.6% versus 1.7% p < 0.0001); There was no difference in one and two year mortality (3.3% versus 3.7%, p = 0.25; 6.3% versus 6.0%, p = 0.5). Long term mortality favored CABG (10.6% versus 9.4%, p = 0.04), particularly in trials of DES era (10.1% versus 8.5%, p = 0.01). In diabetics (n = 3,274) long term mortality favored CABG (13.7% versus 10.3%; p < 0.0001). In six trials of LMCAD (n = 4,700) there was no difference in 30 day mortality (0.6%versus 1.1%, p = 0.15), one year mortality (3% versus 3.7%, p = 0.18), and long term mortality (8.1% versus 8.1%) between PCI and CABG; the incidence of stroke was lower with PCI (0.3% versus 1.5%; p < 0.001). Diabetes and a high SYNTAX score were the subgroups that influenced more adversely the results of PCI. Conclusion: Compared with CABG, PCI using Stents showed lower 30 days mortality, higher late mortality and lower incidence of stroke. Diabetes and a high SYNTAX were the subgroups that influenced more adversely the results of PCI.